Analysis of The Effect of Recruitment, Placement, Training, Job Design, and Work Ethics on Employee Performance - Solikhah, Mar’atus; Dwi Putri Pramesti, Ginna Novarianti (CV. Publikasi Indonesia, 2024)
This rapid progress is inseparable from the management of Human Resources (HR) owned by the company because human resources have an important role in achieving company goals, especially in this era of globalization, where there is tight competition. This study analyzes the influence of recruitment, placement, training, job design, and work ethics variables on employee performance. This study used total sampling for permanent employees because the overall object of research amounted to 42 employees. The results of multiple linear regression analysis showed the positive influence of recruitment (b1=0.573), training (b3=0.309), and work ethics (b5=0.235), as well as the negative influence of placement (b2=-0.221) and job design (b4=-0.222) on employee performance. The partial hypothesis test showed the significance of the variables recruitment (t = 7.994), training (t = 3.155), and work ethics (t = 2.629), while placement (t = -2.463) and job design (t = -2.206) were not significant. Test F shows overall significance (F = 40.504, p <0.05), with a coefficient of determination (R2) of 84.9%, indicating that employee performance is jointly influenced by the variables studied. This research is expected to provide consideration and as policy material related to recruitment, placement, training, job design, and work ethics to improve employee performance.